2006
DOI: 10.1038/sj.onc.1209446
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: p14ARF promotes RB accumulation through inhibition of its Tip60-dependent acetylation

Abstract: p14 ARF is a tumour suppressor which plays a critical role in p53-dependent or -independent cell growth control. Several studies have recently provided evidence that p14 ARF can also interfere either directly or indirectly with some components of the RB signalling pathway to mediate its antiproliferative activity. The aim of this study was to explore the existence of direct relationships between p14 ARF and RB proteins. We show that p14 ARF promotes the accumulation of a hypoacetylated RB protein, when it is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…Previous reports have shown that acetylation of nonhistone proteins may be linked to regulation of their stability (Hernandez-Hernandez et al, 2006;Leduc et al, 2006;Mateo et al, 2009 (Figure 2c). This observation implies that N3 IC is a substrate of HAT-dependent acetylation.…”
Section: Tsa Treatment Regulates Notch3 Signalingmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous reports have shown that acetylation of nonhistone proteins may be linked to regulation of their stability (Hernandez-Hernandez et al, 2006;Leduc et al, 2006;Mateo et al, 2009 (Figure 2c). This observation implies that N3 IC is a substrate of HAT-dependent acetylation.…”
Section: Tsa Treatment Regulates Notch3 Signalingmentioning
confidence: 77%
“…Protein acetylation has been reported to prime subsequent ubiquitin-dependent stability of target proteins (Hernandez-Hernandez et al, 2006;Leduc et al, 2006). Although we and others suggested that proteasomal degradation of Notch intracellular domain (N IC ) may be required for repressing Notch signaling, the underlying mechanisms are still to be clarified.…”
Section: Acetylation Regulates Notch3 Ubiquitination Proteasomal Degmentioning
confidence: 94%
“…The idea that pRB's binding activity is tailored by phosphorylation is only part of the story. Evidence that pRB is both acetylated and methylated in specific contexts (Chan et al 2001;Nguyen et al 2004;Leduc et al 2006;Munro et al 2010;Saddic et al 2010), evidence of interplay between different post-translational modifications (Carr et al 2011;Macdonald and Dick 2012;Munro et al 2012;Kim et al 2015), and evidence that pRB interacts with specific partners in response to cellular cues (MacLellan et al 2000;Miyake et al 2000;Dick and Dyson 2003;Nguyen et al 2004;Carr et al 2014) all suggest additional levels of diversity. Collectively, these observations raise several intriguing possibilities: (1) There may be multiple pools of pRB that perform different functions.…”
Section: How Large Is the Prb Interactome And How Is It Organized?mentioning
confidence: 99%
“…The lysine residues targeted by Tip60 remain to be identified, but as the pRb mutant derivative K873/K874 could still be acetylated, it seems that the residues targeted by Tip60 are distinct from those acetylated by p300 and P/CAF (Leduc et al, 2006). Tip60 interacts with pRb and this triggers its degradation by the proteasome (Leduc et al, 2006). Further, through an unknown mechanism the tumour suppressor protein, p14 ARF prevents Tip60 acetylation of pRb and in turn prevents its degradation (Leduc et al, 2006).…”
Section: Acetylation Of Prbmentioning
confidence: 99%
“…Tip60 interacts with pRb and this triggers its degradation by the proteasome (Leduc et al, 2006). Further, through an unknown mechanism the tumour suppressor protein, p14 ARF prevents Tip60 acetylation of pRb and in turn prevents its degradation (Leduc et al, 2006).…”
Section: Acetylation Of Prbmentioning
confidence: 99%